2016
DOI: 10.1186/s12883-016-0736-7
|View full text |Cite
|
Sign up to set email alerts
|

Asphyxia due to laryngeal spasm as a severe complication of awake deep brain stimulation for Parkinson’s disease: a case report

Abstract: BackgroundIn accordance with German neurosurgical and neurological consensus recommendations, lead placements for deep brain stimulation (DBS) in patients with Parkinson’s disease (PD) are usually performed with the patient awake and in “medication off” state. This allows for optimal lead position adjustment according to the clinical response to intraoperative test stimulation. However, exacerbation of Parkinsonian symptoms after withdrawal of dopaminergic medication may endanger the patient by inducing severe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…JOD is a rare and refractory form of dystonia in Parkinson's syndrome that signi cantly impacts quality of life and can be life-threatening. [1,2,5] Previous studies have indicated improvement in JOD with botulinum toxin or DBS. [1,2] However, botulinum toxin could not completely eliminate JOD and its excessive effectiveness in muscle relaxation risks impairing the ability to eat.…”
Section: Discussionmentioning
confidence: 99%
“…JOD is a rare and refractory form of dystonia in Parkinson's syndrome that signi cantly impacts quality of life and can be life-threatening. [1,2,5] Previous studies have indicated improvement in JOD with botulinum toxin or DBS. [1,2] However, botulinum toxin could not completely eliminate JOD and its excessive effectiveness in muscle relaxation risks impairing the ability to eat.…”
Section: Discussionmentioning
confidence: 99%
“…Cricothyroidotomy was effective only in 40% of cases in the context of ventilation, whereas tracheotomy done by an experienced surgeon was more effective [12]. Respiratory insufficiency, even asystole, was reported by some authors, during AC [12,13]. Various factors can cause respiratory insufficiency, not only the sedative drugs, as commonly believed, but electrical stimulation, neurophysiological monitoring, aspiration, epilepsy with trismus and tongue biting with bleeding, severe comorbidities, obesity, other rear diseases, and medications [13,14] All the above aspects should be analysed individually for candidates for AC [15].…”
Section: Letters To the Editormentioning
confidence: 99%
“…Although uncommon, there are reports of postoperative laryngospasm and respiratory failure in PD. 31,32 Hence, there should be a low threshold to go for chest X-rays, arterial blood gas analysis, and chest physical therapy if PD patients show signs of respiratory abnormalities.…”
Section: Addressing the Common Respiratory And Cardiovascular Complicationsmentioning
confidence: 99%